Educational Video Development with the Help of the Canva Application as an ICT-Based Learning Media in Social Studies Learning for Class VIII of Public Junior High School 1 Pucanglaban - Trias Inang Novanti; Hari Subiyantoro; Yepi Sedya Purwanti (STKIP Taman Siswa Bima, 2025)
Social Studies learning in junior high schools still faces the common problem of low student motivation and creativity due to the dominance of conventional methods and unengaging instructional media. This study aims to develop an educational video using the Canva application as an alternative digital learning media for eighth-grade Social Studies at SMP Negeri 1 Pucanglaban. This research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research instruments included expert validation sheets, teacher and student response questionnaires, creativity tests, and student motivation questionnaires. The validation results indicated that the Canva-based educational video met the criteria of content, visual, and technical validity. Trial results showed that the media was found to be practical for teachers and easily accessible for students via digital devices. Its effectiveness was evident through increased student creativity, demonstrated by indicators of fluency, flexibility, originality, and elaboration. Furthermore, students’ learning motivation also increased significantly, especially in terms of attention, material relevance, self-confidence, and learning satisfaction. Thus, Canva-based educational videos are suitable to be used as innovative Social Studies learning media that promote active engagement and optimal student development.